2018
DOI: 10.1093/mnras/sty1120
|View full text |Cite
|
Sign up to set email alerts
|

A tomographic test of cosmological principle using the JLA compilation of type Ia supernovae

Abstract: We test the cosmological principle by fitting a dipolar modulation of distance modulus and searching for an evolution of this modulation with respect to cosmological redshift. Based on a redshift tomographic method, we divide the Joint Light-curve Analysis compilation of supernovae of type Ia into different redshift bins, and employ a Markov-Chain Monte-Carlo method to infer the anisotropic amplitude and direction in each redshift bin. However, we do not find any significant deviations from the cosmological pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…A similar cosmic anisotropy has been found in the Union2.1 sample (Yang et al 2014;Javanmardi et al 2015;Bengaly et al 2015;Li et al 2015;Lin et al 2016b). Different with the Union2 or Union2.1 sample, the JLA sample doesn't show any convincing evidence for the existence of the cosmic anisotropy (Bengaly et al 2015;Lin et al 2016a;Chang et al 2018a;Wang & Wang 2018;Deng & Wei 2018b;Sun & Wang 2018a). Constraining the anisotropic amplitude and direction in ΛCDM, ωCDM and CPL models with the JLA sample gave a zero result (Lin et al 2016a).…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…A similar cosmic anisotropy has been found in the Union2.1 sample (Yang et al 2014;Javanmardi et al 2015;Bengaly et al 2015;Li et al 2015;Lin et al 2016b). Different with the Union2 or Union2.1 sample, the JLA sample doesn't show any convincing evidence for the existence of the cosmic anisotropy (Bengaly et al 2015;Lin et al 2016a;Chang et al 2018a;Wang & Wang 2018;Deng & Wei 2018b;Sun & Wang 2018a). Constraining the anisotropic amplitude and direction in ΛCDM, ωCDM and CPL models with the JLA sample gave a zero result (Lin et al 2016a).…”
Section: Introductionmentioning
confidence: 51%
“…Constraining the anisotropic amplitude and direction in ΛCDM, ωCDM and CPL models with the JLA sample gave a zero result (Lin et al 2016a). No significant deviation from the isotropic universe was found through a redshift tomographic analysis on the JLA sample in the dipole-modulated ΛCDM model (Chang et al 2018a). Constrained by the JLA sample, an anisotropic universe model with Bianchi-I metric was found to be consistent with the isotropic universe (Wang & Wang 2018).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Zhao et al found a dipole of cosmic acceleration at more than 2σ level with the Union2 sample [100]. Unlike the Union2&2.1 sample, there is no anisotropic signal in the JLA sample [101][102][103] and Pantheon sample [104][105][106]. Zhao and Zhou et al [107] found that the SDSS 0123456789().…”
Section: Introductionmentioning
confidence: 99%
“…After that, Mariano and Perivolaropoulos (Mariano & Perivolaropoulos 2012) found a possible preferred anisotropic direction at the 2σ level using the Union2 sample, but by employing the dipole fitting (DF) method. Since then, these two methods have been widely used to explore the cosmic anisotropy (Cai & Tuo 2012;Cai et al 2013;Zhao et al 2013;Li et al 2013;Heneka et al 2014;Bengaly et al 2015;Andrade et al 2018;Sun & Wang 2019) by investigating observational data of, for instance, the Union2.1 sample (Yang et al 2014;Javanmardi et al 2015;Lin et al 2016a), the Joint Light-Curve Analysis (JLA) sample (Lin et al 2016b;Chang et al 2018a;, the Pantheon sample (Sun & Wang 2018), gamma-ray bursts (GRBs; Wang & Wang 2014), galaxies (Zhou et al 2017), as well as gravitational wave and fast radio bursts (Qiang et al 2019;Cai et al 2019). Using HC and DF methods, Zhao et al (2019) studied the cosmic anisotropy via the Pantheon sample.…”
Section: Introductionmentioning
confidence: 99%